Climate Change and Urban Resilience in Smart Cities: Adaptation and Mitigation Strategies in Brazil and Germany - Roberto Schoproni Bichueti; Walter Leal Filho; Clandia Maffini Gomes; Jordana Marques Kneipp; Carlos Rafael Röhrig da Costa; Kamila Frizzo (Urban Science)
Urban resilience is crucial in academic and policy discussions, particularly in balancing urban development and sustainability in both developed and developing countries. In developing nations, rising emissions and vulnerability challenge effective climate change mitigation and adaptation efforts. Advances in Information and Communication Technologies offer significant opportunities despite challenges. The digital revolution is central to enhancing urban management, especially in smart cities. In light of this context, this paper aims to investigate the literature advancements of urban resilience to climate change in smart cities and conduct a multi-case study analysis of adaptation and mitigation strategies in Brazilian and German smart cities, demonstrating their efforts to enhance urban resilience to climate challenges. The research used two main methods: a bibliometric analysis to review literature on climate change, urban resilience, and smart cities, and case studies of urban resilience practices in 10 smart cities from Brazil and Germany. The literature review highlights the increase in research on this theme, identifying five thematic clusters that reveal relationships among study topics and suggest future research directions. The cases highlighted local initiatives in Brazilian and German smart cities to enhance urban resilience to climate pressures, revealing notable differences due to varying levels of development and investment.